Interpenetrating interfaces for efficient perovskite solar cells with high operational stability and mechanical robustness - Qingshun Dong (Nature Portfolio, 2021)
Operational stability and mechanical robustness remain as engineering bottlenecks in perovskite solar cells technology. Here, Dong et al. introduce an interpenetrating perovskite at the electron-transporting-layer interface that enables a 1000-hour stable operation and high endurance against bending fatigue over 2500 cycles.